Influence of shading on the carbohydrates and phenols in cattley guava cuttin - Junior, João Guilherme Casagrande; Bianchi, Valmor João; Strelow, Eder Zarnott; Bacarin, Marcos Antonio; Fachinello, José Carlos (Pesquisa Agropecuaria Brasileira, 1999)
The present work proposed to evaluate the influence of shading on the non-structural carbohydrates and total soluble phenols in leaves and stem of cutting, collected from cattley guava (Psidium cattleyanum Sabine) stock plant. The half-wood cuttings were collected in November of 1996, in plants kept under different shading levels (30, 50 e 70% of reducing light ) and plants kept full sun. The content of total and reducing soluble carbohydrates, starch and total soluble phenols were determined on the leaves and on the stem of each cutting. It was observed that with the increase of shading, there was a raise on starch content and a decrease on reducing carbohydrates content both on leaves and stems. Only on the stem a decrease on total soluble carbohydrates content was observed. The content of phenolic composts were reduced remarkably in the leaves with the increase of shading percentage. In the stems, a small reduction, not significant, was verified, confirming that plants at low sun radiation change their content of store and phenolic composts.
Keywords: Psidium cattleyanum; luminosity; store substances; phenolic composts